202k views
4 votes
If f(x)=-3x+3, then f^-1 (x)=____
Please help

If f(x)=-3x+3, then f^-1 (x)=____ Please help-example-1
User Randolph
by
5.2k points

1 Answer

7 votes

Answer:

y = (-x/3) +1 or y = (-1/3 * x) + 1

Explanation:

For the inverse of a function, you invert the y and x positions.

In your case:

y = -3x+3

The inverted function is:

x = -3y+3

When you solve this for y, you get:

-3y = x-3

y = -x/3 +1

User Omar Abdelhafith
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.